Multiple malignant epithelioid mesotheliomas of the liver and greater omentum: a case report and review of the literature - Koji Minami; Hiroshi Okumura; Kiyokazu Hiwatashi; Sumika Matsukita; Tetsuro Setoyama; Kota Minamimagari; Yusuke Tsuruta; Ichiro Kanetsuki; Yoshito Ogura; Shigeho Maenohara; Shoji Natsugoe (Surgical Case Reports)
Abstract Background Malignant mesothelioma commonly arises from the pleura, but can also arise from the peritoneum, pericardium, and tunica vaginalis testis. However, malignant mesothelioma of the liver is extremely rare and coexistence with malignant mesothelioma of the greater omentum has not been described in the literature. In this case report, we present a case of multiple malignant mesothelioma of the liver and greater omentum. Case presentation A 36-year-old woman was admitted to our hospital for the evaluation of an elastic hard mass in the right upper abdomen. Abdominal contrast computed tomography showed a cystic mass measuring 13 × 14 × 11 cm in the right liver lobe with enhanced mural nodule. Abnormal accumulation was identified in the liver and lower abdominal area on 18F-fluorodeoxyglucose positron emission tomography. The patient underwent hepatectomy of the posterior segment and partial resection of the omentum. The final pathological diagnosis was low-grade multiple malignant epithelioid mesothelioma based on characteristic immunohistochemical findings. As of 6 months postoperatively, the patient has shown no disease recurrence. Conclusions We present the first case of a 36-year-old woman with multiple malignant mesothelioma of the liver and greater omentum.